(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The goals of this study are to assess the field performance, character association, variability, and genetic diversity of 50 bitter gourd (Momordica charantia L.) accessions collected from various locations of Bangladesh. To evaluate the morphological and qualitative characteristics, as well as to assess the genotypic and phenotypic variability and correlation, the study employed a randomized complete block design (RCBD) with three replications. MC022 exhibited the highest yield (2.50 kg/plant), MC080 in number of fruits per plant (35.67), and MC079 in average fruit weight (101.69 g) among all accessions. Numbers of flowers per plant (99.14), petiole (97.84), vine length (97.81), and yield per plant (94.08) exhibited high heritability with genotypic and phenotypic coefficients of variation. The maximum phenotypic variance (4676.60) and genotypic variance (4574.40) were both recorded at vine length. The average fruit weight was significantly positively correlated with the yield per plant at both the genotypic (r = 0.873**) and phenotypic (r = 0.861**) levels. Cluster I contained the most accessions (14). No limitations were detected. It can be concluded that bitter gourd accessions exhibit a diverse array of qualitative and morphological traits. In addition, the yield of different bitter gourd accessions was correlated with an assortment of yield-contributing attributes. The genotypic coefficient of variation was less than the phenotypic coefficient of variation in all of the traits. Fruit length, average fruit weight, number of fruits per plant, and yield per plant were found to have higher values and lower differences between phenotypic and genotypic co-efficient of variation, indicating a high potential for selecting superior accessions. J Bangladesh Agril Univ 23(2): 99–112, 2025